A Novel Model of Partial Discharge Initiation in Cable Insulation - Gen Li; Jie Chen; Hongze Li; Libin Hu; Wenjun Zhou; Chengke Zhou (IEEE Access, 2022)
Urban power transmission and distribution rely on safe operation of vast network of power cables. Majority cable insulation defects can result in partial discharge (PD), which is therefore a degradation mechanism as well as a good indicator of cable insulation condition. Previously published PD models, however, failed to help quantitatively evaluate the insulation condition, or they fail to help differentiate those in between the conditions which are safe to operate from those which may need urgent testing or inspection. PD mechanisms in power cables are reviewed first in this paper. Then a novel model which is based on F distribution is proposed aiming to classify the PD activities which may be associated with different level of degradation. This is based on previous reports that PD activities manifests differently when the levels of degradation of the defect site(s) progress. After that, the features and effects of the model are presented with a case study, and the model is verified by analyzing the waveform similarities. Finally, the nature of the model is compared with the abc-model and the dipole model, demonstrating that proposed model can uniquely recognize the three stages of PD defect development.